Corruption and economic growth in Africa: the impact on development - Abdulai, David N. (Routledge studies in development economics, 2024)
Corruption is one of the major challenges impeding Africa's growth and development efforts and its impact is much more pronounced at this point of the continent's development trajectory. Corruption has political, economic, and social consequences and this book argues that any efforts to help Africa grow and develop must prioritise the fight against it, so that the aid and funding given for projects in the region can continue to be sustained. The book also tackles the issue of national security and instability caused by corruption. The author argues that progress cannot happen in countries and environments where instability exists and persists. Corruption in Africa has contributed to instability and other national security challenges, especially in fragile states on the continent. The book starts by looking at the three major types of corruption: petty, grand, and systemic and then goes on to address the different categories of corruption such as bureaucratic, legislative, political, as well as public and private sector aspects. It also deals with common forms of corruption as well as some of the causes, such as bad governance and excessive greed, to mention a few. Further, it critically examines how current political systems on the continent contribute to this condition. The book argues that some of the solutions that have been proposed to date are not viable or have not worked in practice, and through applied research, offers workable solutions that policy makers, African politicians, academics, and students of economics and development can use as a reference guide in the fight against corruption